International Monetary Fund (IMF) - Viterbo, Annamaria (Kluwer Law International B.V., 2019)
Derived from the renowned multi-volume 'International Encyclopaedia of Laws', this systematic analysis of the structure, competence, and management of the International Monetary Fund (IMF) provides substantial and readily accessible information for lawyers, academics, and policymakers likely to have dealings with its activities and data. No other book gives such a clear, uncomplicated description of the organization?s role, its rules and how they are applied, its place in the framework of international law, or its relations with other organizations.00The monograph proceeds logically from the organization?s genesis and historical development to the structure of its membership, its various organs and their mandates, its role in intergovernmental cooperation, and its interaction with decisions taken at the national level. Its competence, its financial management, and the nature and applicability of its data and publications are fully described.